2014
DOI: 10.1155/2014/420858
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Headache/Migraine: The Importance of Weight Reduction through Lifestyle Modifications

Abstract: The aim of this study is to determine a possible relationship between prevalence, frequency, and severity of migraine and obesity. All pertinent data from the literature have been critically examined and reviewed in order to assess the possible relationship between obesity and migraine, in particular migraine frequency and disability in children, as well as in adult population studies. Prevalence, frequency, and severity of migraine appear to increase in relation to the body mass index, although this evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
0
25
2
1
Order By: Relevance
“…83,153 A recent systematic review suggested that "clinicians should have a special interest for weight reduction" of obese patients with migraines. 154 Upper and lower-extremity pain Numerous systematic reviews and high-quality RCTs in patients with OA have documented the benefit of physical rehabilitation on both weight loss and OA status. One well-performed study suggested that a modest reduction in weight through diet and exercise resulted in greater improvements in pain and physical performance in obese and overweight patients with knee OA compared with gains with either treatment alone.…”
Section: Headachesmentioning
confidence: 99%
“…83,153 A recent systematic review suggested that "clinicians should have a special interest for weight reduction" of obese patients with migraines. 154 Upper and lower-extremity pain Numerous systematic reviews and high-quality RCTs in patients with OA have documented the benefit of physical rehabilitation on both weight loss and OA status. One well-performed study suggested that a modest reduction in weight through diet and exercise resulted in greater improvements in pain and physical performance in obese and overweight patients with knee OA compared with gains with either treatment alone.…”
Section: Headachesmentioning
confidence: 99%
“…As patient body mass index (BMI) increases, it stands to reason that there would be more subcutaneous fat separating targeted muscle groups from the skin surface, such that the standard 0.5-inch needle may no longer be able to penetrate deeply enough to allow intramuscular injection. Given that obesity is associated with increased migraine prevalence, frequency, and disability, 20 we believe that a patient's BMI may be important for treatment planning in order to ensure effective intramuscular uptake of toxin. To our knowledge, this is the first study to examine the relationship between BMI and the distance from skin to muscle fascia at various botulinum toxin injection sites.…”
mentioning
confidence: 99%
“…Headache prevalence and frequency is related to BMI (body mass index) in many studies (25). Foods that deliver slowly avail-…”
Section: Discussionmentioning
confidence: 99%